2014
DOI: 10.3389/fgene.2014.00202
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automated motion-tracking analysis of locomotion speed in the C. elegans transgenics overexpressing beta-amyloid in neurons

Abstract: Multi-Worm Tracker (MWT) is a real-time computer vision system that can simultaneously quantify motional patterns of multiple worms. MWT provides several behavioral parameters, including analysis of accurate real-time locomotion speed in the nematode, Caenorhabditis elegans. Here, we determined locomotion speed of the Alzheimer's disease (AD) transgenic strain that over-expresses human beta-amyloid1-42 (Aβ) in the neurons. The MWT analysis showed that the AD strain logged a slower average speed than the wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…It is well documented that the transgenic expression of human Aβ in the body wall muscle cells of C. elegans results in progressive paralysis [57,498]. We found that either 1% glucose or 1% glycerol alleviated paralysis in Aβ transgenic worms.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…It is well documented that the transgenic expression of human Aβ in the body wall muscle cells of C. elegans results in progressive paralysis [57,498]. We found that either 1% glucose or 1% glycerol alleviated paralysis in Aβ transgenic worms.…”
Section: Discussionmentioning
confidence: 50%
“…Machino et al found lower fecundity and increased egg hatching time in neuronal Aβ expressing worms. [498]. We find that both glucose and glycerol induced further dose-dependent impairment of fecundity and egg viability in worms that express Aβ in neurons.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations